Producción bajo riego de cultivares de pasto ovillo (Dactylis glomerata L.) en Patagonia Norte - Gallego, Juan Jose; Barbarossa, Raul Antonio; Miñon, Daniel Pedro; Murray, Francisco (EEA Valle Inferior, INTA, 2025)
EEA Valle Inferior